Identification of landslide vulnerable zones in West Khasi District of Meghalaya - Bose Mahalingam; Indraddin; De Trisha; Channabasappa K. (E3S Web of Conferences)
A landslide is a mass of rock, debris, or earth moving down a slope. Landslides are a form of mass waste under the direct influence of gravity, indicating any down-slope movement of rock and soil. Landslide encompasses five forms of slope movement: topples, falls, spreads, slides, and flows. Landslides are the large-scale movement of rock, debris, or earth down a slope. The present study was conducted to identify the landslide-vulnerable zones in the West Khasi District of Meghalaya. In total, nine parameters were chosen to assess the vulnerability, such as geology, geomorphology, lithology, elevation, slope, lineament, rainfall, land use and land cover, and soil. These parameters were classified into five groups and ranked between 1 and 5, in which the value 1 indicates highly vulnerable, and the value 5 indicates less vulnerable. Further, the overall weightage for each parameter was computed using AHP. Then, a weighted overlay analysis was carried out in ArcGIS Pro. The result was classified into five classes: very high to very low vulnerable areas. The result showed that a larger area of the district is covered by moderate vulnerability.